Isatuximab plus carfilzomib and dexamethasone versus carfilzomib and dexamethasone in elderly patients with relapsed multiple myeloma: IKEMA subgroup analysis - Facon, Thierry; Moreau, Philippe; Martin, Thomas G; Spicka, Ivan; Oriol, Albert; Koh, Youngil; Lim, Andrew; Mikala, Gabor; Rosiñol, Laura; Yağci, Münci; Cavo, Michele; Yong, Kwee; et al. (Hematological oncology, 2022)
In this subgroup analysis of the randomized, Phase 3 IKEMA study (NCT03275285), we evaluated efficacy and safety of the anti-CD38 monoclonal antibody isatuximab (Isa) in combination with carfilzomib-dexamethasone (Isa-Kd) versus Kd in older (≥70 years of age, n = 86) and younger (<70 years, n = 216) patients with relapsed multiple myeloma (MM). Patients received Isa 10 mg/kg intravenously weekly for 4 weeks, then every 2 weeks in the Isa-Kd arm, and approved schedule of carfilzomib (twice weekly) and dexamethasone in both study arms. Primary endpoint was progression-free survival (PFS); key secondary efficacy endpoints included rates of overall response (ORR), very good partial response or better (≥VGPR), minimal residual disease negativity (MRD-), and complete response (CR). Addition of Isa to Kd resulted in improved PFS in elderly patients (hazard ratio, 0.36 [95% CI, 0.18-0.75]) consistent with the significant PFS improvement observed in the overall IKEMA population. Treatment with Isa-Kd improved depth of response versus Kd, with higher rates of ≥VGPR (73.1% vs. 55.9%), MRD- (23.1% vs. 11.8%), and CR (38.5% vs. 23.5%). Although the incidence of grade ≥3 treatment-emergent adverse events (TEAEs) was higher in Isa-Kd, the incidence of serious TEAEs was similar between arms. Fewer elderly patients definitively discontinued treatment due to TEAEs in Isa-Kd than Kd: 11.8% versus 23.5%. In conclusion, Isa-Kd provides a consistent benefit versus Kd in elderly patients, with a manageable safety profile, and represents a new treatment option for patients with relapsed MM, independent of age.
Keywords: Humans; monoclonal antibody; multiple myeloma; senioři nad 80 let; dexamethason; Multiple Myeloma; Aged, 80 and over; mnohočetný myelom; senioři; Aged; CD38; Dexamethasone; isatuximab; lidé; elderly